DNA barcodes for Cladocera and Copepoda from Mexico and Guatemala, highlights and new discoveries - Elías-Gutiérrez, Manuel; Jerónimo, Fernando Martínez; Ivanova, Natalia V.; Valdez-Moreno, Martha; Hebert, Paul D. N. (Zootaxa, 2008)
DNA barcoding, based on sequence diversity in the mitochondrial COI gene, has proven an excellent tool for identifying species in many animal groups. Here, we report the first barcode studies for freshwater zooplankton from Mexico and Guatemala and discuss the taxonomic and biological implications of this work. Our studies examined 61 species of Cladocera and 21 of Copepoda, about 40% of the known fauna in this region. Sequence divergences among conspecific individuals of cladocerans and copepods averaged 0.82% and 0.79%, respectively, while sequence divergences among congeneric taxa were on average 15-20 times as high. Barcodes were successful in discriminating all species in our study, but sequences for Mexican Daphnia exilis overlapped with those of D. spinulata from Argentina. Our barcode data revealed evidence of many species overlooked by current classification systems —for example, based on COI genotypes the Diapahanosoma birgei group appears to include 5 species, while Ceriodaphnia cf. rigaudi, Moina cf. micrura, Mastigodiaptomus albuquerquensis and Mastigodiaptomus reidae all include 2–3 taxa. The barcode results support recent taxonomic revisions, such as recognition of the genus Leberis, and the presence of several species in the D. birgei and Chydorus sphaericus complexes. The present results indicate that DNA barcoding will provide powerful new insights into both the incidence of cryptic species and a better understanding of zooplankton distributions, aiding evaluation of the factors influencing competitive outcomes, and the colonization of aquatic environments.